2020
DOI: 10.3390/coatings10020130
|View full text |Cite
|
Sign up to set email alerts
|

Fully Reversible Electrically Induced Photochromic-Like Behaviour of Ag:TiO2 Thin Films

Abstract: A TiO2 thin film, prepared on fluorine-doped indium tin oxide (FTO)-coated glass substrate, from commercial off-the-shelf terpinol-based paste, was used to directly adsorb Ag plasmonic nanoparticles capped with polyvinylpyrollidone (PVP) coating. The TiO2 film was sintered before the surface entrapment of Ag nanoparticles. The composite was evaluated in terms of spectroelectrochemical measurements, cyclic voltammetry as well as structural methods such as scanning electron microscopy (SEM), transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In contrast, the current density–time curves of the darkish films (Fig. 11b) show good photocurrent density close to that of FTO 29 and Ag: TiO 2 thin films 30 for potential photovoltaic applications. The film produced at 600 mJ per pulse turned out to be optimum with the highest current density, indicating that the film performance has little to do with the FTO underneath.…”
Section: Resultsmentioning
confidence: 83%
“…In contrast, the current density–time curves of the darkish films (Fig. 11b) show good photocurrent density close to that of FTO 29 and Ag: TiO 2 thin films 30 for potential photovoltaic applications. The film produced at 600 mJ per pulse turned out to be optimum with the highest current density, indicating that the film performance has little to do with the FTO underneath.…”
Section: Resultsmentioning
confidence: 83%
“…Ammar et al [13] used ZnO nanoclusters for the detection of chloroform (CHCl 3 ) using density functional theory calculations implemented in a Gaussian 09 program. The results revealed that ZnO nanoclusters with a specific geometry and composition are promising candidates for CHCl 3 -sensing applications.…”
Section: This Special Issuementioning
confidence: 99%
“…Anxious to release the soldiers employed in the Jewish camps, military authorities questioned the use of keeping the 'illegal immigrants' in Cyprus while Jews were airlifted from Europe, particularly Czechoslovakia, to Israel where they immediately integrated combat units without any apparent opposition from the UN Mediator, Count Folke Bernadotte. 115 Writing at a time when debates over the establishment of constitutional government deeply polarized the island, 116 the Governor of Cyprus was quick to agree, highlighting that the continued presence of Jews in Cyprus 'raise the cost of living and prevent a return to normal price levels' and 'constitute a constant threat to the political tranquility of the island'. He ventured to add that the British government should not 'worry too much about what the Arabs would say' as they had 'lost out any way and the Jewish State ha[d] come to stay'.…”
Section: The Time Of the 'Detainees' 1946-1949mentioning
confidence: 99%